Empowering Digital Literacy through Wattpad: Bridging Creativity, Reading, and Writing in Education - Reflina Sinaga; Sondang Erita Simanjuntak; Medina Novita Ginting; Florentina Tarigan; Agustariana Br Pinem (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community service investigates the impact of Wattpad, a social media platform, on students' interest, creativity and digital literacy within the framework of the digital literacy movement. Results show that Wattpad positively influences students' engagement in reading and writing, offering a space for aspiring writers to showcase their ideas and fostering constructive communication between writers and readers. Wattpad's digital literacy potential is clear in its aspirations as a digital service provider, helping students access diverse literary content and resources. This study emphasizes the need for careful management of content to conform to moral and literacy standards. Wattpad has tremendous promise as a digital literacy tool, especially in educational settings. Integrating Wattpad into formal education curricula can offer deep literacy experiences, foster creativity, critical thinking, and meet the needs of the ever-evolving modern digital world. In conclusion, this research underscores the importance of digital literacy in the current era and positions Wattpad as a valuable tool for developing literacy skills, creativity, and fostering a love for reading and writing among students.